O desenvolvimento do ser pessoal em Edith Stein. (2021)
The development of the personal being in Edith Stein. From the nucleus to the formation of the person Abstract This paper analyses Stein's conception of personal development that happens from a nucleus, a personal center. Stein already identifies this nucleus in phenomenological writings, as a personal structure, synonymous of his own individuality, constituted by soul self. The concept of the nucleus will be developed at a later stage of his thinking in which she elaborates an ontology in an anthropological key. The nucleus informs the soul and the body during the process. Unlike Tomas de Aquino, individuality isn’t given by the body (matter); but by the form, from within. Development comprises the whole of the person, both interiority and exteriority. However, it will be in the personal and unique relationship of the human being with the divine being, that the nucleus, understood as the ‘essence of the soul’, will open fully and will get to know that specific image or ‘qualitative mark’ that is yours. The full unfolding of the nucleus would be in the capacity to love God and to love our neighbour. Key words: personal development, nucleus, individuality, person, sou